ANALISIS KEYAKINAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PERSAMAAN LINEAR SATU VARIABEL - Siti Fatimah; Agung Hartoyo; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to analyze students' mathematical beliefs in resolving word problems on the one-variable linear equation material based on the level of students' mathematical abilities. This research used qualitative methods with case study research. The data were obtained from the results of the word problems test, questionnaire, and interview. The subjects in this study were 6 students, consist of 2 students with high mathematical abilities, 2 students with medium mathematics abilities, and 2 students with low mathematics abilities. Selection of subjects based on report cards for the even semester in the academic year 2019/2020. The results showed that 1) 1 highly capable subject was able to comply five of the six mathematical belief scales, namely difficult problems, understanding, the importance of word problems, effort, and usefulness of mathematics, while 1 other subject was able to comply four of the six mathematical belief scales, namely difficult problems, understanding, effort, and usefulness of mathematics 2) 1 medium capable subject is able to comply four of the six mathematical belief scales, namely difficult problems, understanding, the importance of word problems, effort, and usefulness of mathematics, while 1 other subject is able to comply five of the six mathematical belief scales, namely difficult problems, understanding, importance word problem, effort, and usefulness of mathematics. 3) 1 lowly capable subject is able to comply three of the six mathematical belief scales, namely difficult problems, the importance of word problems, and effort, while 1 other subject is only able to comply two of the six mathematical belief scales, namely the effort and usefulness of mathematics. Keywords: Mathematical Ability, Mathematical Beliefs, Resolving Word Problems